A phylogenetic reappraisal of Excipulariopsis narsapurensis in Wiesneriomycetaceae, Tubeufiales - Paraparath, Sruthi O.; Rajkumar, Sakshi; Rajeshkumar, Kunhiraman C.; Verma, Rajnish K.; Gautam, Ajay Kumar; Narula, Bhavna; Wijayawardene, Nalin N.; Tibpromma, Saowaluck; Karunarathna, Samantha C. (Phytotaxa, 2023)
The monotypic genus Excipulariopsis, with type species E. narsapurensis, was established based on the emended generic characteristics of Excipularia narsapurensis. Excipulariopsis has non-cupulated superficial conidiomata arising directly from stroma surrounded by thick walled dark brown subulate setae. The conidia are dark brown, broadly fusoid, having thick septa and truncate base. Phylogenetic analyses using ITS, LSU, TEF1α and RPB2 sequences positioned Excipulariopsis allied to Speiropsis in the family Wiesneriomycetaceae, as a sister family to Tubeufiaceae within Tubeufiales. This study resolved a long-standing ambiguity about the phylogenetic status of this unique sporodochial setose hyphomycetes from India.